EKSPLORASI ORNAMEN PENGERET RET TERHADAP KONSEP BANGUN DATAR - Ribka Zelin Margaretha Sitepu; Hardi Tambunan; Ruth Mayasari Simanjuntak (Universitas Nias Raya, 2025)
This study aims to explore the relationship between the traditional pengeret-ret ornament and the concept of plane figures from an ethnomathematical perspective. The pengeret-ret ornament, a distinctive motif from the cultural heritage of the Indonesian archipelago, was chosen as the object of study due to its rich visual patterns filled with geometric shapes. This research employs a literature study method with a qualitative-descriptive approach. Data sources include scholarly journals, ethnographic articles, and visual references of relevant traditional motifs. The findings indicate that the pengeret-ret ornament contains elements of plane figures such as triangles, squares, parallelograms, rhombuses, and circles. These patterns are arranged symmetrically and repetitively, reflecting geometric concepts such as translation, reflection, and rotation. In addition to their aesthetic and symbolic value, these ornaments also hold great potential as contextual, culturally based media for teaching geometry. Therefore, this research contributes to the development of ethnomathematics teaching materials as well as the preservation of culture through innovative approaches in mathematics education.